Implementation of Digital Literacy Based Hybrid Classes in Islamic Education (PAI) Study Programs in Higher Education - Darliana Sormin; Muksana Pasaribu; Riski Ananta; Nor Kalsum Mohd Isa (Yayasan Adra Karima Hubbi, 2026)
Background: The rapid development of digital technology has encouraged universities to integrate technology into the learning process, including in Islamic education. The implementation of hybrid classes has become an innovative learning solution that combines online and offline learning to enhance the digital literacy of students and lecturers. However, the implementation of hybrid learning in the Islamic Education Study Program still requires the development of an effective model aligned with Islamic educational values. Purpose: This study aims to develop a hybrid class-based Islamic education model to improve the digital literacy skills of the academic community in the Islamic Education Study Program, Faculty of Islamic Studies, Muhammadiyah University of South Tapanuli. Method: This study employed a qualitative approach using the Plomp Model, which consists of the stages of Planning, Learning, Organizing, Operating, Monitoring, and Product. Data were collected through observation, interviews, and documentation, and then analyzed through data reduction, data presentation, and conclusion drawing. Results: The findings revealed that the implementation of hybrid classes significantly improved students' digital literacy skills, lecturers' competencies in utilizing learning technology, and the overall quality of digital-based learning within the faculty. Hybrid learning also encouraged active student participation through the use of Learning Management Systems (LMS), virtual discussions, and collaborative digital projects. Conclusion: The hybrid class-based Islamic education development model proved effective in enhancing digital literacy and supporting learning transformation that is relevant to technological advancements while maintaining Islamic educational values.